Shared Resource Laboratory Operations: Changes Made During Initial Global COVID‐19 Lockdown of 2020. Issue 1 (27th November 2020) - Back, Jessica B.; Chadick, Cora H.; Garcia Vallejo, Juan J.; Orlowski‐Oliver, Eva; Patel, Radhika; Roe, Caroline E.; Srivastava, Jane; Walker, Rachael V.
Abstract: Undoubtedly, the global pandemic caused by the SARS‐CoV‐2 virus has had a significant impact on Shared Resource Laboratories (SRL) operations worldwide. Unlike other crises (e.g., natural disasters, acts of war, or terrorism) which often result in a sudden and sustained cessation of scientific research usually affecting one or two cities at a time, this impact is being seen simultaneously in every SRL worldwide albeit to a varying degree. The alterations to SRL operations caused by the COVID‐19 pandemic can generally be divided into three categories: (1) complete shutdown, (2) partial shutdown, and (3) uninterrupted operations. In many cases, SRLs that remained partially or fully operational during the initial wave of global infections saw a concurrent increase in COVID‐19‐related research coming through their facilities. This forced SRLs to make rapid adjustments to core operations at the same time as infectious disease experts were still developing recommendations for the safety of frontline medical workers. Although many SRLs already had contingency plans in place, this pandemic has highlighted the importance of having such plans for continuity of service, if possible, during a crisis. Immediate changes have occurred in the way SRLs operate due to potential virus transmission and in line with this new "Best Practices" have been established, that is, social distancing, remote working, and technology‐based meetings and training. Many of these changes are likely to be in place for some time with the threat of further waves of infections toward the end of 2020 and into 2021. Some of these best practices, such as having many training resources recorded and available online, are likely to remain long‐term. Although many changes have been made in haste, these will alter the future operations of SRLs. In addition, we have learnt how to deal with future crises that may be encountered in the workplace. © 2020 The Authors. Cytometry Part A published by Wiley Periodicals LLC. on behalf of International Society for Advancement of Cytometry.